PERAN GURU DALAM MEMBENTUK KESADARAN GENDER BERKEADILAN SEJAK DINI DI KB/TK IT CAHAYA UMMAT - Sinias Mawarni Gulo; Nufitriani Kartika Dewi; Swantyka, Swantyka Ilham Prahesti; Syifa, Syifa Fauziah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to describe teachers’ roles, identify instructional strategies, and analyze the supporting and inhibiting factors in developing gender equity awareness among young children at KB/TK IT Cahaya Ummat Bergas. This study employed a qualitative descriptive approach. The data were obtained from five informants consisting of one headteacher, two teachers, and two parents. The researcher collected the data through non-participant observation, guided flexible interviews, and documentation. The data were analyzed through data reduction, data display, conclusion drawing, and verification. Data trustworthiness was established through credibility, transferability, dependability, and confirmability. The findings showed that teachers served as role models of equitable behavior, facilitators of fairness values, guides of social interaction, protectors of emotional safety, and evaluators of children’s development. Teachers developed gender equity awareness through storytelling, role-play, simple discussions, thematic and collaborative activities, heterogeneous groups, open-ended questions, social-emotional approaches, and learning media representing diverse social roles. The implementation was supported by the headteacher’s commitment, teachers’ competence and collaboration, school regulations, parental support, an inclusive environment, learning media, and religious values. The process was constrained by children’s limited understanding of abstract concepts, teachers’ difficulties in simplifying language, the number of students, stereotypical comments from the surrounding environment, established habits, and parents’ limited time. The study concluded that teacher role-modelling, integrated instructional strategies, and consistent habituation across school and family environments contributed to the development of gender equity awareness from an early age. Keywords:teacher roles, gender equity awareness, early childhood, instructional strategies, early childhood education